2012 4th Electronic System-Integration Technology Conference 2012
DOI: 10.1109/estc.2012.6542097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bonding pressure on quality of SLID interconnects

Abstract: The investigation of the bonding pressure change on the different quality aspects of the solid-liquid interdiffusion (SLID) interconnects is presented. The stacks were produced by a flux-assisted bonding of two Si dies with an area array of square Cu/SnAg bumps on the bottom die and Cu bumps on the top die at approx. 250 °C. The bonding pressure was varied between 0 MPa, 0.35 MPa, 0.69 MPa, 1.04 MPa, 1.38 MPa, 1.73 MPa, 2.08 MPa, 2.42 MPa. Cross-sections of the stacks were analyzed by optical microscopy and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our experiments have shown that the transition to Cu 3 Sn is incomplete when a shorter annealing time is used, for example 15 min, which will result in a bond line with both Cu 5 Sn 6 and Cu 3 Sn present. The Sn overflow region is smaller than 5 μm, where the Sn rich alloy Cu 6 Sn 5 is the major remaining [1,5,7]. Another benefit of using the two-step temperature bonding profile is the formation of void-free bonding interfaces, since it could prevent the fast diffusion between Cu and Sn.…”
Section: Wafer-level Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiments have shown that the transition to Cu 3 Sn is incomplete when a shorter annealing time is used, for example 15 min, which will result in a bond line with both Cu 5 Sn 6 and Cu 3 Sn present. The Sn overflow region is smaller than 5 μm, where the Sn rich alloy Cu 6 Sn 5 is the major remaining [1,5,7]. Another benefit of using the two-step temperature bonding profile is the formation of void-free bonding interfaces, since it could prevent the fast diffusion between Cu and Sn.…”
Section: Wafer-level Processesmentioning
confidence: 99%
“…The IR transmission microscopy presents a relatively small Sn overflow in the metallic structure of the sealed lines (see figure 1(b). Comparing this with one-step or even three step bonding processes, the type II process leads to the formation of micro-joints with controllable Sn overflows [6][7][8][9][10].…”
Section: Wafer-level Processesmentioning
confidence: 99%
See 1 more Smart Citation